THE EFFECT OF FINANCIAL DISRESS ON STOCK PRICES WITH EARNINGS MANAGEMENT AS A MODERATING VARIABLE - Sri Mulyati; Asep Kurniawan; Rosida Rosida (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
The purpose of this study was to determine the effect of financial distress on stock prices with earnings management as a moderating variable. The population in this study were 41 Hotel, Restaurant and Tourism Sub-Sector Companies Listed on the Indonesia Stock Exchange (quarter 1, quarter 2, quarter 3 and quarter 4) before the COVID-19 pandemic and in 2020 (quarter 1, quarter 2, quarter 3 and quarter 4) and during the COVID-19 pandemic). Based on the purposive sampling method, the samples used were 20 companies. The hypothesis in this study was tested using multiple linear regression and MRA. The results of the first hypothesis from this study indicate that financial distress has a significant negative effect on stock prices with the results of the t-test known that the t-count value (-2.569) > t table (-1.654) and the significance level (0.011) <0.10. The results of the second hypothesis show that earnings management has a significant positive effect on stock prices with the results of the t count (1.874) > t table (1.654) and the significance level (0.063) < 0.10. The results of the third hypothesis show that earnings management as a moderating variable does not affect the effect of financial distress on stock prices, which means that earnings management does not strengthen or weaken the level of financial distress on stock prices with a significant value of 0.423 greater than the error tolerance value = 0.10